Chieftaincy as religion: a conjectural interpretation of its role in the decolonization process in “Northern Angola” - Florescu, Madalina (Africana Studia, 2020)
In this paper it is argued that colonization and decolonization are not only about changes at the level of the concrete sociopolitical reality but also at the level of how domains of “possibility” or “potentiality” are created, and this involves the imaginary that mediates how subjects perceive themselves in relation to others, institutions, and the environment. Thus, for the purpose of analysis, “chieftaincy” has been replaced with “religion” as defined in J. D. Y. Peel’s (2000) terms as the imagination of the realm beyond mundane perception by means of which individuals make sense of their experience using the resources available to them. Keywords: religion, boundaries, decolonization, semiotic interpretation, Angola